2010
DOI: 10.1039/b921582d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the addition of colloidal iridium oxide into sol–gel obtained titanium and ruthenium oxide coatings on titanium on their electrochemical properties

Abstract: Electrochemical properties of sol-gel processed Ti(0.6)Ir(0.4)O(2) and Ti(0.6)Ru(0.3)Ir(0.1)O(2) coatings on titanium substrate were investigated using cyclic voltammetry, polarization measurements and electrochemical impedance spectroscopy and compared to the properties of Ti(0.6)Ru(0.4)O(2) coating. The role of iridium oxide in the improvement of the electrocatalytic, capacitive and stability properties of titanium anodes activated by a RuO(2)-TiO(2) coating is discussed. The oxide sols were prepared by forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The investigation showed that finely dispersed iridium oxide was produced by the sol-gel procedure. 13 It was found by an accelerated stability test in sea water that the ternary coating was considerably more stable during exploitation than the binary one. 12 This was assigned to the greater stability of nano-sized IrO 2 under vigorous oxygen and chlorine evolution in comparison to sol-gel processed RuO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation showed that finely dispersed iridium oxide was produced by the sol-gel procedure. 13 It was found by an accelerated stability test in sea water that the ternary coating was considerably more stable during exploitation than the binary one. 12 This was assigned to the greater stability of nano-sized IrO 2 under vigorous oxygen and chlorine evolution in comparison to sol-gel processed RuO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…EXPERIMENTAL Colloidal dispersions of ruthenium, iridium and titanium oxide were obtained by the forced hydrolysis of the corresponding metal chlorides in boiling 0.27 mol dm -3 HCl. 11,13 The dispersions of RuO 2 , IrO 2 and TiO 2 (oxide sols) were formed during 46, 20 and 10 h (ageing times), respectively. These ageing times were chosen since Ti 0.6 Ru 0.4 O 2 coatings with the best electrochemical properties were obtained from sols of these ageing times, 9 while the ageing time of IrO 2 was set in-between.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the noble metal loading in PEM water electrolysis (PEMWE) cells, some multicomponent electrocatalysts usually prepared by combining one or more less-expensive metal oxides such as Ta 2 O 5 [18], TiO 2 [19], SnO 2 [20], and Sb 2 O 5 -SnO 2 [21] where Ir oxide are frequently reported. As a matter of fact, these Ir-based multi-component electrocatalysts usually show inferior OER performance, unless Ir is richly contained (>80-70 at.%), mainly due to the OER inertia and poor conductivity of these non-noble metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…EIS has been employed in kinetic studies of chlorine evolution on platinum [11][12][13] but not on DSA electrodes. It has been used to characterize DSA anodes in low concentration chloride solutions [14][15][16][17][18][19][20][21] at low potentials, 1.05 V vs Ag/AgCl to 1.18 V vs Ag/AgCl, 22,23 which corresponds to current densities up to 10 mA cm −2 . These conditions are far from those used industrially for producing chlorine, where the current densities reach 400 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%